A molecularly imprinted polymer-based evanescent wave fiber optic sensor for the detection of basic red 9 dye - Foguel, Marcos V. [UNESP] (2015)
A cheap and robust method for the detection and quantification of textile dyes is the use of biomimetic sensors with optical transduction, employing a molecularly imprinted polymer (MIP) as the recognition element. This paper presents the optimization of a MIP for the dye, basic red 9 (BR9) and the immobilization of these polymers on a disposable 4-cm long polystyrene optical waveguide for the development of an evanescent wave fiber optic sensor aimed at the determination and quantification of this dye in different matrices and industrial effluents. MIPs were synthesized using 2-acrylamido-2-methyl-1-propanesulfonic acid and ethylene glycol dimethacrylate, as functional monomer and cross-linker, respectively. The polymer was then immobilized on the waveguide by dip-coating the fiber in the polymer suspension. The sensing element was interrogated with a fiber-coupled spectrophotometer. BR9 could be detected in the low μM range, thus making it a promising device for determining this compound in textile effluents.